(3UjO GdNGWQ ef efMI GdaGWQs ((3HgfGe GdeSjMi GdeJWHH s)
(3ChdgG (B:s
(3hHYO , aGdQZHI Edi Gddg JYGdi ai EOGeI GjGe ehdGfG Gdehdi GdYRjR GdN hdeG QCi GdYHO GdVYja s
(3BNQgG (B:s
(3hGdYdGLGJ COhjI eCdhaI SdjeI , adfMeO Gddg Ydi jfHhY fYeg s
(3hgh eQJH Ydi YTQ ebGdGJ eaUdIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
GALS - (3GdLRA (B1 - (3U (B919 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B123 s
Keywords: (3GdWHs